External Supervision Of The Judicial Commission Of Judges In Indonesia - Herry Febriadi (Scholar Center, 2023)
Writing this made for knowing effectiveness Commission Judicial in supervision against judges in Indonesia and the causes Thing that . Case - case prosecution of judges who violate code judge ethics and violate law already Becomes phenomenon moment this . Method research used _ in this article is